Is It Really a Paradox? A Mixed-Methods, Within-Country Analysis of the Gender Gap in STEM Education - Islam Abu-Asaad; Maria Charles; Yariv Feniger; Gila Manevich-Malul; Halleli Pinson (Social Sciences)
It is well established that women’s representation in scientific and technical fields decreases with societal affluence, but the mechanisms underlying this so-called paradox remain contested. This study leverages distinctive features of the Israeli educational system to identify social psychological and organizational mechanisms driving contextual variability in the gendering of physics and computing subjects. Using in-depth interviews and original surveys, we compare gender gaps in ninth graders’ attitudes and aspirations across two highly segregated yet centrally administered state school sectors: one serving the socioeconomically marginalized Arab Palestinian minority, and one serving the Jewish secular majority. Results reveal curricular affinities, discourses, and course-taking patterns that are differentially gendered across school sectors. While boys and girls in Arab Palestinian schools report more instrumentalist motivations and more positive attitudes toward mathematically intensive fields, students in Jewish schools engage in highly gendered, self-reflexive discourses that support gendered course-taking. Findings support arguments positing gender-specific effects of postmaterialist, individualistic value systems, and suggest that the cultural and organizational processes that generate larger gender gaps in more affluent countries may also play out within countries.